Role of testosterone and androgen receptor in periodontal disease progression in female rats - Steffens, João Paulo; Valenga, Henrique Meister; Santana, Luis Carlos Leal [UNESP]; Albaricci, Maria Carolina da Costa [UNESP]; Kantarci, Alpdogan; Spolidorio, Luis Carlos [UNESP] (Wiley, 2020)
Background: Sex hormone therapy has strict recommendations in the treatment of postmenopausal symptoms, in which testosterone (TES) replacement may play a potential role. However, it remains unclear whether TES affects the course of chronic inflammation and alveolar bone loss in females. Herein, we investigated the role of androgen receptor and TES on the inflammatory response and alveolar bone resorption associated with ligature-induced periodontal disease in female rats. Methods: Fifty female Holtzman rats were divided in five groups (n = 10/group): androgen receptor antagonist (flutamide); estrogen receptor antagonist (fulvestrant); TES supplementation; aromatase inhibitor (anastrozole); and TES plus anastrozole. Periodontitis was induced by ligatures around the lower first molars for 2 weeks. Twenty animals (n = 10/group) were used as untreated ligated or non-ligated controls. Bone loss and the number of osteoclasts were measured through radiographic and immunohistochemical analysis, respectively. Inflammatory cytokines, chemokines and bone markers were measured by multiplex immunoassay and ELISA in serum samples and periodontal tissues. Results: The blockage of androgen receptor significantly increased radiographic bone loss and tissue levels of IL-1α (P <0.05), IL-1β (P <0.001) and IL-10 (P <0.01) compared with the periodontitis group. Testosterone supplementation significantly increased EGF levels in tissue samples, whereas when combined with aromatase inhibitor anastrozole significantly increased both EGF and VEGF (P <0.05). None of the treatment conditions significantly impacted the number of osteoclasts compared with the periodontitis group. Conclusions: Androgen receptor activation is an important factor in the regulation of several inflammatory markers, and its blockage significantly increases bone loss.
Keywords: alveolar bone loss; androgen receptor antagonists; aromatase inhibitors; estrogen antagonists; inflammation; testosterone